The Role of Temperature on Morphological Properties of Gallium Nanowires: A Kinetic Monte Carlo Study - Putungan, Darwin B.; Albao, Mavin A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 22 No 1 (2010), 2011)
In this work, we investigated the effects of temperature on the morphological properties, specifically homogeneous to heterogeneous island ratio R and mean island size, of Ga one-dimensional nanowires through Kinetic Monte Carlo (KMC) simulations. Relevant simulation parameters and inputs were first calculated using Density Functional Theory (DFT) methods. The system was treated via an atomistic-lattice gas model which includes necessary atomistic processes. KMC implementation of the model was carried out to simulate the growth and evolution of Ga nanowires. The ratio R was found to increase as the temperature was increased, whereas the mean island size decreases for the same temperature trend. These observations were explained by taking note that the increase in thermal energy effected enhanced homogeneous nucleation, outnumbering heterogeneous islands, due to the increased frequency of adatom collisions. On the other hand, enhanced homogenous nucleation impacts the mean island size by favoring creation of new islands rather than making existing islands grow in length.
Keywords: Density Functional Theory, Kinetic Monte Carlo, Self-assembly